Cyber-risk and youth: digital citizenship, privacy, and surveillance - Adorjan, Michael (Routledge studies in crime and society, 2019)
Introduction -- Research focus and methodology -- Teens online : what and why -- Youth attitudes and experiences towards parental and school surveillance -- Relational aggression -- Privacy mindsets -- Gender, sexting and the teenaged years -- Policies, practices and concluding thoughts